PELARUTAN SILIKA PADA FRAKSI KUARSA KAOLIN MENGGUNAKAN Burkholderia cenocepacia - Azhar, Annisa Sylvania; Wahyuni, Nelly; Sayekti, Endah (Tanjungpura University, 2024)
Dissolution of silica (SiOâ‚‚) from its insoluble form to a soluble form is crucial for enhancing its availability as precursor material. This study aimed to compare the effectiveness of silica dissolution by the bacterium Burkholderia cenocepacia producing organic acids (citrate, oxalate, acetate) and potassium hydroxide (KOH). Variations in incubation times using Burkholderia cenocepacia at 24, 96, and 192 hours were applied to samples of quartz-kaolin fractions and silica sand. The concentration of dissolved silica was measured using ICP-OES. The results showed maximum dissolution by B. cenocepacia in quartz-kaolin at 0.8493 mg/L (96 hours) and silica sand at 0.8638 mg/L (24 h). The dissolved silica from this procedure can be further processed for applications in agriculture as a nutrient for plants to overcome biotic and abiotic stress.